Clinical Features of Restless Legs Syndrome - J Gordon Millichap (Pediatric Neurology Briefs, 2004)
Clinical characteristics of childhood-onset restless legs syndrome (RLS) were studied in 32 (5.9%) patients, <18 years of age, diagnosed with the disorder among 538 who attended the Pediatric Sleep Disorders Center with sleep-wake complaints, between January 2000 and March 2004, at the Mayo Clinic, Rochester, MN.